Representasi Gibran Rakabuming Dalam Dinamika Pemakzulan Wakil Presiden Pada Sampul Majalah Tempo Edisi 5 – 11 Mei 2025 - Yuwono, Andri Prasetyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
This study analyzes the representation of Gibran Rakabuming Raka in the political context of the vice presidential impeachment discourse, as depicted on the cover of Tempo Magazine, edition May 5–11, 2025, titled